2021
DOI: 10.1002/crq.21305
|View full text |Cite
|
Sign up to set email alerts
|

Engaging complex diversity in academic institution: The case of “triple periphery” in a context of a divided society

Abstract: This research examines how faculty members working in complex sociopolitical context cope with campus diversity. Through 20 focus groups comprised of faculty members representing all of the departments at one academic institution, we investigated the participants' experiences with student diversity. The findings show that the protracted Israeli–Palestinian conflict seeps into classroom interactions. This infiltration of the protracted conflict is particularly salient during escalations of the conflict. The par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…The interviews suggest that in times of stronger political tension, attitudes toward Jewish-Israeli students tend to be more negative and separation between the groups grows. The findings confirm previous findings about the infiltration of the Israeli-Palestinian conflict into classroom interactions (Raz Rotem et al, 2021), and about stronger stereotyping behavior among Jewish-Israeli students toward Palestinian students in times of conflict compared to more peaceful times (Bar-Tal & Labin, 2001). Following that, our study showed that although the university can provide a valuable space for Palestinian students to learn about their Jewish counterparts, the constraints of asymmetry and political tension remain and continue to influence the quality of interactions.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The interviews suggest that in times of stronger political tension, attitudes toward Jewish-Israeli students tend to be more negative and separation between the groups grows. The findings confirm previous findings about the infiltration of the Israeli-Palestinian conflict into classroom interactions (Raz Rotem et al, 2021), and about stronger stereotyping behavior among Jewish-Israeli students toward Palestinian students in times of conflict compared to more peaceful times (Bar-Tal & Labin, 2001). Following that, our study showed that although the university can provide a valuable space for Palestinian students to learn about their Jewish counterparts, the constraints of asymmetry and political tension remain and continue to influence the quality of interactions.…”
Section: Discussionsupporting
confidence: 90%
“…Our interviewees reported facing initial difficulties and described how they reshaped their own cultural identities, learned to cope with stressful interpersonal situations and gained an improved understanding of the other. In this sense, the university can provide a special space that allows for encounters between groups in a volatile intergroup situation as sensitive as that involving the Arab‐Palestinian minority and the Jewish majority in Israel, particularly in the potentially explosive situation of Jewish‐Palestinian relations in Jerusalem (de Vries & Majlaton, 2021; Desivilya et al, 2017; Hager & Jabareen, 2016; Raz Rotem et al, 2021). The picture that emerges from the interviews indicates that the asymmetry and separation present in society seem to be reflected in a university context as well.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations